PROSES ASIMILASI PADA BAHASA SUMBAWA: FONOLOGI GENERATIF - Aulia Wildaan Sela; Nurhayati Nurhayati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2020)
Abstrak. This study examines the assimilation process in the Sumbawa language with the aim of describing the assimilation process in the Sumbawa language. This research method is included in the type of descriptive qualitative. In that Sumbawa consists of several assimilation processes, the process studied includes receiving sounds and sound dissolution. N sound is needed in Sumbawa language, the process of switching nasal sounds occurs when the vowel sound suffixes on the stem which means ownership. Furthermore, there is a sound impingement process at the beginning, middle and end. Sounding at the beginning occurs at the sound s, t, and w the sounding occurs before the vowel sound on the stem. The middle sound is displayed on the sound of n sounding then the sound [?] . And sound attenuation at the end occurs in the sound of this obscuring vowel occurring after the sound [t], [s], [m]. In addition, the sounding factor in the Sumbawa language can also be used to assist in supporting and discussing the conversation.